Hubungan Asupan Zat Gizi Makro, Kualitas Tidur, dan Aktivitas Fisik Dengan Status Gizi pada Remaja di SMP Negeri 14 Bandar Lampung - Nabilah, Disa; Agatha, Annisa; Dalimunthe, Nathasa Khalida (Journal of Education Religion Humanities and Multidiciplinary, 2024)
WHO (2018) reported a significant increase in the prevalence of overweight among children and adolescents aged 5-19, rising from just 4% in 1975 to over 18% in 2016. This increase was observed in both genders, with 18% in females and 19% in males. The Lampung Health Survey (Riskesdas Lampung) in 2018 reported that the prevalence of nutritional status (BMI/U) among adolescents aged 13-15 in Lampung Province showed 8.84% were very underweight, 79.28% were normal, and 11.9% were overweight and obese. For the age group of 16-18 years, 7.5% were very underweight and underweight, 80.9% were normal, and 11.6% were overweight and obese. In Bandar Lampung, the prevalence rate reached 14.8%, higher than the provincial average. Adolescence, which generally spans the ages of 10 to 19, is a critical transition period from childhood to adulthood, characterized by biological changes including growth in height and weight, and sexual maturation. The general objective of this study was to determine the correlation between macro nutrient consumption, sleep quality, and physical activity with the nutritional status of adolescents at SMP Negeri 14 Bandar Lampung. This study employed an observational analytic method with a Cross-Sectional approach. The study population included all adolescents in grade VIII at SMP Negeri 14 Bandar Lampung, totaling 101 samples. The sampling technique used was Simple Random Sampling. Data on macro nutrient consumption were obtained using a 2x24 hour food recall questionnaire. Sleep quality data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Physical activity data were gathered using a physical activity questionnaire. Body weight was measured using a digital scale, and height was measured using a microtoise. Data analysis was conducted using the chi-square test. The study findings indicated a correlation between macro nutrient consumption and nutritional status (p = 0.000), a correlation between sleep quality and nutritional status (p = 0.000), and a correlation between physical activity and nutritional status (p = 0.000). It is hoped that adolescents can regulate their physical activity patterns, dietary patterns, and sleep patterns to prevent changes in nutritional status, whether undernutrition or overnutrition.